Pelatihan Pembelajaran Inovatif Bagi Guru untuk Mewujudkan Peserta Didik Yang Cerdas, Sehat, dan Bahagia - Gunawan Gunawan; Ni Made Yeni Suranti; Hamsu Kadriyan; Qothrunnada Qothrunnada; Baiq Nabila Saufika Zainuri (Indonesian Journal of Education and Community Services, 2026)
Teachers are instrumental in advancing 21st-century education and implementing Indonesia's Merdeka Curriculum, which emphasizes the integration of cognitive development, mental resilience, and a positive learning environment. However, teachers in Alas District, Sumbawa Regency, continue to face challenges in designing innovative learning that promotes Higher Order Thinking Skills (HOTS) and mental health literacy. This community service program aimed to enhance teachers' understanding and practical competencies in implementing innovative learning grounded in mental health literacy. The program was conducted offline through the University of Mataram's Mental Health Literacy Research Product Dissemination Program and involved 60 teachers from early childhood, primary, junior secondary, and senior secondary education levels. The implementation consisted of coordination, training sessions (lectures, discussions, sharing sessions, and a Kahoot-based quiz), and observation-based evaluation. The findings revealed high participant engagement and enthusiasm while fostering a collaborative forum for exchanging best teaching practices to support students' cognitive development, mental well-being, and overall happiness.